MyoGestic: EMG interfacing framework for decoding multiple spared motor dimensions in individuals with neural lesions - Simpetru, Raul; Braun, Dominik; Simon, Arndt; März, Michael; Cnejevici, Vlad; Souza de Oliveira, Daniela; Weber, Nico; Walter, Jonas; Franke, Jörg; Höglinger, Daniel; Prahm, Cosima; Ponfick, Matthias; et al. (Science Advances, 2025)
Restoring motor function in individuals with spinal cord injuries (SCIs), strokes, or amputations is a crucial challenge. Recent studies show that spared motor neurons can still be voluntarily controlled using surface electromyography (EMG), even without visible movement. To harness these signals, we developed a wireless, high-density EMG bracelet and a software framework, MyoGestic. Our system enables rapid adaptation of machine learning models to users’ needs, allowing real-time decoding of spared motor dimensions. In our study, we successfully decoded motor intent from two participants with traumatic SCI, two with spinal stroke, and three with amputations in real time, achieving multiple controllable motor dimensions within minutes. The decoded neural signals could control a digitally rendered hand, an orthosis, a prosthesis, or a two-dimensional cursor. MyoGestic’s participant-centered approach allows a collaborative and iterative development of myocontrol algorithms, bridging the gap between researcher and participant, to advance intuitive EMG interfaces for neural lesion